PENGARUH REWARD, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN TITIK TERANG KONVEKSI - Bayu Ramdhani (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to examine and analyze the effect of rewards, job satisfaction, organizational commitment, and organizational citizenship behavior (OCB) on employees of the Bright Point of Convection. The sample in this study was 50 employees of the Bright Point of Convection. The sampling technique used is the census technique, which is a technique that can be accessed by data that is achieved by collecting the required information from all related population units contained in the population. The analytical method used in this study using multiple linear regression models, with the help of the SSS test instrument version 23.0. The data testing technique used in this study includes validity testing, reliability testing with Cronbach alpha. classical assumption test and multiple linear analysis, to test and prove research. The results of the analysis show that there is a positive and significant effect of Reward on Organizational Citizenship Behavior (OCB), there is an insignificant effect of Job Satisfaction on Organizational Citizenship Behavior (OCB), there is a positive and significant effect of Organizational Commitment on Organizational Citizenship Behavior (OCB). And with the results of the f test (Goodness of fit) states that Rewards, Job Satisfaction, Organizational Commitment, simultaneously (together) have a significant positive effect on and Organizational Citizenship Behavior (OCB) on employees of the Bright Point of Convection. Keywords : Reward; Job Satisfaction; Organizational Commitment; Organizational Citizenship Behavior (OCB)